2005
DOI: 10.1111/j.1365-2486.2005.000999.x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and food web structure of soil decomposer community as affected by the size of habitat fragment and habitat corridors

Abstract: While most ecologists agree that the effects of fragmentation on diversity of organisms are predominantly negative and that the scale of fragmentation defines their severity, the role of habitat corridors in mitigating those effects still remains controversial. This ambiguousness rests largely on various difficulties in experimentation, a problem partially solved in the present paper by the use of easily manipulated soil communities. In this 2.5-year-long field experiment, we investigated the responses of soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…For example, small‐scale experiments have suggested that habitat fragmentation may change predator‐prey dynamics and soil food web structure (Holyoak and Lawler , Rantalainen et al. ). In addition, fragmentation may also affect the distribution of hosts for obligatory parasitic or mutualistic fungal taxa (Cordeiro and Howe ), movement patterns of fungal vectors, and the availability of other abiotic or biotic factors, which may also contribute to disparate responses to habitat fragmentation among fungal groups that differ in life‐history strategies (Sato et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, small‐scale experiments have suggested that habitat fragmentation may change predator‐prey dynamics and soil food web structure (Holyoak and Lawler , Rantalainen et al. ). In addition, fragmentation may also affect the distribution of hosts for obligatory parasitic or mutualistic fungal taxa (Cordeiro and Howe ), movement patterns of fungal vectors, and the availability of other abiotic or biotic factors, which may also contribute to disparate responses to habitat fragmentation among fungal groups that differ in life‐history strategies (Sato et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dispersal range of microbes by soil fauna might be quite limited, this distance seems not without significance in respect to the tiny size of microorganisms and microbial competition within the tight network of roots in dense stands of established vegetation. Similarly Rantalainen et al (2004) demonstrated in a laboratory study an important role of enchytraeids in spreading saprophytic fungi between habitat patches through corridors, but in a successive field study it was shown that most fungi had quite good dispersal abilities via hyphal growth independent of soil faunal activity (Rantalainen et al 2005). At present, evidence suggests nematodes as being important vectors of bacteria, whereas fungivores appear to have more important roles as consumers than as vectors of fungi in the rhizosphere.…”
Section: Soil Fauna As Vectors Of Rhizosphere Microorganismsmentioning
confidence: 96%
“…The understanding of area–species diversity relationships is of utmost and practical importance as they allow prediction of the negative impact of habitat fragmentation on biodiversity (Gaston & Spicer, 1998). The effect of habitat fragmentation on soil biodiversity has been directly addressed in a few studies focusing on microarthropods (Rantalainen et al. , 2005), termites (Fonseca De Souza & Brown, 1994), ants (Suarez et al.…”
Section: Global and Landscape Patterns Of Soil Biodiversity Distributionmentioning
confidence: 99%